2007
DOI: 10.1128/jcm.01334-06
|View full text |Cite
|
Sign up to set email alerts
|

First Case of Human Babesiosis in Korea: Detection and Characterization of a Novel Type of Babesia sp. (KO1) Similar to Ovine Babesia

Abstract: We report on the first case of human babesiosis in Korea. The intraerythrocytic parasite (KO1) in the patient's blood mainly appeared as paired pyriforms and ring forms; but Maltese cross forms were not seen, and the parasite showed morphological features consistent with those of the genus Babesia sensu stricto. The sequence of the 18S rRNA gene of KO1 was closely related to that of Babesia spp. isolated from sheep in China (similarity, 98%). The present study provides the first evidence of the presence of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 22 publications
1
89
0
2
Order By: Relevance
“…The results from the epidemiological evaluation, using PCRTeq, N/PCRTeq and M/PCRTeq-Bc (Table 3), characterize an endemic situation comparable to what was observed in surveys on horses in Minas Gerais, Goiás, São Paulo and Mato Grosso do Sul, using PCR techniques (Heim et al 2007, Kim et al 2007). In other countries in which T. equi is endemic, frequencies similar to those observed in this study have been found, also using PCR (Rüegg et al 2007, Jaffer et al 2009).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The results from the epidemiological evaluation, using PCRTeq, N/PCRTeq and M/PCRTeq-Bc (Table 3), characterize an endemic situation comparable to what was observed in surveys on horses in Minas Gerais, Goiás, São Paulo and Mato Grosso do Sul, using PCR techniques (Heim et al 2007, Kim et al 2007). In other countries in which T. equi is endemic, frequencies similar to those observed in this study have been found, also using PCR (Rüegg et al 2007, Jaffer et al 2009).…”
Section: Resultssupporting
confidence: 70%
“…The greater capacity of nested PCR for identifying naturally infected horses is due to the fact that this technique detects smallersized parasitemia (6x10 -6 % to 8x10 -6 %) than does conventional PCR (only down to 8x10 -5 %) (Bashiruddin et al 1999, Nicolaiwsky et al 2001, Baldani et al 2008. So far, only real-time PCR has been described as having sensitivity greater than or equal to nested PCR (Kim et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of the SSU rDNA of this isolate (KO1) determined that it was similar to a Babesia parasite isolated from sheep in China (322). In Taiwan, Shih et al (518) discovered an asymptomatic infection with a species of Babesia in a 51-year-old woman.…”
Section: Babesia Sppmentioning
confidence: 99%
“…Examples include WA1, EU1, CA1, MO1, KO, and KY (35,114,322,574). However, based on molecular and immunological evidence, some of these acronyms are now known to represent the same species (114,574).…”
Section: Babesia Sppmentioning
confidence: 99%
“…Babesia species are tick-borne haemoprotozoan parasites that infect virtually all mammalian species, with significant economic consequences in domestic animals and human health implications, particularly in the USA [52,53]. In mice, B. microti induces high but transient parasitaemias, which are quickly cleared (clearance beginning approximately 10 days after infection) [54].…”
Section: Materials and Methods (A) Methods Overviewmentioning
confidence: 99%